1. The problem statement, all variables and given/known data h(t) = √t (1 - t^2) 2. Relevant equations the product rule is (first) x (derivative of the second) + (second) x (derivative of the first) 3. The attempt at a solution i've been working at this for a while. the closest answer i came up with was this: h(t)= t^1/2 (t^1/2 - t^5/2) h'(t)= 1/2t^1/2 (1/2t^1/2 - 5/2 t^3/2) h'(t) = 1 (1 - 5 t^3/2)/2t^1/2 h'(t) = 1 - 5t^3/2 / 2t^1/2 (the actual solution is 1 - 5t^2 / 2t^1/2) if anyone could show me where i went wrong with this, it would be MUCH appreciated. thanks!